Manajemen Full Day School dalam Pembentukan Karakter Peserta Didik di SD Islam Terpadu Nurul Fikri Sidoarjo - Dian Arsista; Ahmad Hariyadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to explain the management of Full Day School in shaping the character of students at SD IT Nurul Fikri Sidoarjo. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results show that Full Day School management is implemented through three main stages: planning, implementation, and evaluation. In the planning stage, the school formulates visions, missions, and goals focused on developing students' character values. Organization is carried out by clearly assigning duties and authorities to the principal, teachers, and educational staff so that each party can perform their roles in a directed and coordinated manner. Implementation involves integrating character values into learning activities, religious practices, extracurricular programs, and teacher role modeling. Evaluation is conducted regularly through work meetings to review achievements and identify challenges. Supporting programs for character development include habituation of worship such as congregational prayers and tahfidz, social activities, extracurricular programs, and Character Building Life Skills (CBLS), which instill values of independence, leadership, and responsibility. These activities are designed not only to support students’ daily routines but also to instill moral values applicable in daily life. The active role of teachers, staff, and the school environment significantly contributes to the program’s effectiveness, creating an educational system that balances academic aspects with consistent character development.